Evolution of regional scientific collaboration networks: China-Europe emerging collaborations on nano-science. (1st January 2013) - Chen, Yantai; Assimakopoulos, Dimitris; Xie, Hongming; Chi, Renyong
This study analyses the dynamics of regional scientific collaboration networks between Chinese and European regions on the emerging nano-science field. Using data on the co-author publications between Chinese and European nano-scientists for the period 1990–2011, the results enable us to identify the evolutionary and active collaboration networks between China and Europe. The driving forces for engaging cross-border regional collaboration networks are identified between a new global science polar and a traditional scientific superpower. This analysis suggests that the rapid and uneven growth of scientific collaboration networks between China and European Union membership nation's evolutes, which resulting from multiple factors. Implications for promoting global-regional collaborations among scientists' communities are discussed.